2017
DOI: 10.1007/s40262-017-0587-4
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors in the Treatment of Triple-Negative Breast Cancer

Abstract: Breast cancer is a heterogeneous disease, manifesting in a broad differentiation in phenotypes and morphologic profiles, resulting in variable clinical behavior. Between 10 and 20% of all breast cancers are triple negative. Triple-negative breast cancer (TNBC) lacks the expression of human epidermal growth factor receptor 2 (HER2) and hormone receptors; therefore, to date, chemotherapy remains the backbone of treatment. TNBC tends to be aggressive and has a high histological grade, resulting in a poor 5-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 80 publications
1
78
0
1
Order By: Relevance
“…Some genomic alterations identified in TNBC tumors are associated with various responses to chemotherapy and targeted therapies (11,12). However, no mutations or chromosomal rearrangements in TNBC tumors have been found that confer resistance to specific chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some genomic alterations identified in TNBC tumors are associated with various responses to chemotherapy and targeted therapies (11,12). However, no mutations or chromosomal rearrangements in TNBC tumors have been found that confer resistance to specific chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…As a key component in the DNA repair machinery, the poly (ADP-Ribose) polymerase (PARP) is a main target during chemotherapies and radiation therapies in cancer cells (31,118). The PARP family plays a pivotal role in diverse cellular processes, and their inhibitors are therapeutic agents in the treatment of breast cancer (53,75). An interesting study has shown that HNO donors elicit strong…”
Section: Role Of Hno Donors or Its Derivatives In Different Cancersmentioning
confidence: 99%
“…PARP inhibitors are promising agents for the treatment of BL-1 (basal-like 1) TNBC, which features an enriched cell cycle, elevated DNA damage response (ATR/BRCA), proliferation pathway, and cell-cycle checkpoint loss pathways [ 97 ]. PARP inhibitors serve as a group of novel oral anticancer drugs that are highly active in TNBC with selected mutations or epigenetic silencing of genes involved in the DNA damage response (DDR), including BRCA1 and BRCA2 [ 98 ]. However, PARP inhibitors can upregulate PD-L1 expression and enhance cancer-associated immunosuppression.…”
Section: Combination Of Immune Checkpoint Inhibitors With Targeted Trmentioning
confidence: 99%